Residual Effect of Nitrogen Fertilization on Nitrous Oxide Flux and Yield of Three Cowpea Varieties (Vigna unguiculata L.) in Rainfed Rice Fields - Wihardjaka, Anicetus (JOURNAL OF TROPICAL SOILS, 2018)
Nitrogen fertilizer use in rainfed rice fields is generally less efficient, only part of N is taken up by plants for their gowth and other N is lost and fixed by soil particles. Nitrogen loss in the form of nitrous oxide can reduce N fertilizer use efficiency and contribute to the increase of atmospheric greenhouse gases emission. The field experiment was conducted to determine the residual effect of N fertilizer on nitrous oxide (N2O) flux and yield of some cowpea varieties (Vigna unguiculata) in rainfed rice fields. The experiment was arranged in a factorial randomized block design with three replicates. The first factor was three cowpea varieties (KT 9, KT 6, KT 3), while the second factor was four levels of residual inorganic N fertilizer (0, 90, 135, 180 kg N ha-1). The variables measured were N2O fluxes, grain yield, biomass weight, total N content in soil before planting cowpea, available N in soil after harvesting cowpea. Residual N fertilizer increased significantly N2O emission from cowpea cropping. Nitrous oxide emission from plots grown with cowpea variety of KT 9, KT 6, and KT 3 ranged 0.42-0.69, 0.30-2.64, and 0.09-2.19 kg N2O ha-1, respectively. N losses from soil grown with KT 9 was lower than those in plots grown with other varieties. Residual effect of N fertilizer increased available N in soil as much as 11.6-82.3% (KT 9), 7.6-30.6 % (KT 6), and 9.6-67.9% (KT 3), recpectively. Residual effect of N fertilizer increased significantly grain yield of KT 9, KT 6, and KT 3 varieties as much as 45.7-111.8%, 79.8-89.3%, and 6.9-25.4%, respectively.